2013
DOI: 10.1007/s10995-012-1200-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Youth Violence in the U.S., 1999–2009: Ethnic Comparisons and Disaggregating Asian Americans and Pacific Islanders

Abstract: This study examined ethnic and gender differences in youth violence in the U.S. across time, especially when disaggregating Asian Americans and Pacific Islanders and examining adolescents with mixed ancestry. National data from 1999 to 2009 of the Centers for Disease Control and Prevention's Youth Risk Behavior Surveillance System were analyzed. The analyses were performed on individual items and three factors (i.e., carry weapon, felt unsafe, fights). Overall, 43.9 % responded to at least one indicator of vio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…According to the 2009 Youth Risk Behavioral Survey (YRBS) results, NHOPI youths are at higher risk of violence victimization and perpetration (see Table 1) (Centers for Disease Control and Prevention, 2009). These trends have been consistent for the past decade (Sugimoto-Matsuda, Hishinuma, and Chang, 2011;Wong et al, 2011).…”
Section: Violence and Substance Use Among Native Hawaiian And Pacific...supporting
confidence: 56%
“…According to the 2009 Youth Risk Behavioral Survey (YRBS) results, NHOPI youths are at higher risk of violence victimization and perpetration (see Table 1) (Centers for Disease Control and Prevention, 2009). These trends have been consistent for the past decade (Sugimoto-Matsuda, Hishinuma, and Chang, 2011;Wong et al, 2011).…”
Section: Violence and Substance Use Among Native Hawaiian And Pacific...supporting
confidence: 56%
“…Studies that disaggregate the Asian American and Pacific Islander population have found racial/ethnic disparities similar to our study. A national study of the YRBS from 1999 to 2009 found that Native Hawaiian and other Pacific Islander youth are more likely to carry weapons, feel unsafe, and engage in fighting than youth of other ethnicities (Sugimoto-Matsuda, Hishinuma, & Chang, 2013). In Hawai‘i-based research, Mayeda, Chesney-Lind, and Koo (2001) found that Native Hawaiian and Samoan youth self-reported higher rates of overall risky behavior (e.g., violence, delinquency, property offense, and substance use) compared with youth of other ethnicities.…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings have indicated that, when disaggregated, there are substantial ethnic differences in youth violence rates among AAPI populations (Mayeda et al 2006). AAPI youth suffer disproportionately from youth violence when compared to national averages, with Pacific Islanders having among the highest youth violence rates among six nonmixed races in the U.S. based on all youth violence items of the 1999-2007 Youth Risk Behavior Surveillance System (YRBSS; Centers for Disease Control and Prevention [CDC]; Sugimoto-Matsuda et al 2010). Theories for the high rates of youth violence for AAPIs include marginalization through colonialism, effects of low socioeconomic status, discrimination, mental illness stigma, and cultural conflict between Western and more collectivistic values (Mayeda et al 2006;Le 2002;Mark and Nishigaya 2009;Mark et al 2005).…”
Section: Introductionmentioning
confidence: 99%